Pengaruh Lokasi dan Kualitas Pelayanan terhadap Kepuasan Konsumen - Rahman Aziez Herdian; Cece Rakhmat; Suci Putri Lestari (Politeknik Baubau, 2022)
This study aims to determine the effect of partially and simultaneously the influence of location and service quality on customer satisfaction at Tasik Aquarium Stores. The method used in this research is descriptive research with quantitative methods. The sample issued is 100 respondents. The data collected consists of primary and secondary data. Data analysis in this study used multiple linear regression, assessment analysis, coefficient of determination analysis using SPSS version 25 software. The results showed that location and service quality simultaneously had a significant role on consumer satisfaction at Tasik Consumer Stores. Partially, the location and quality of service have a significant effect on consumer satisfaction at the Tasik Aquarium Store.